'Click'‐xylosides as initiators of the biosynthesis of glycosaminoglycans: Comparison of mono‐xylosides with xylobiosides. (2nd November 2016) - Chatron‐Colliet, Aurore; Brusa, Charlotte; Bertin‐Jung, Isabelle; Gulberti, Sandrine; Ramalanjaona, Nick; Fournel‐Gigleux, Sylvie; Brézillon, Stéphane; Muzard, Murielle; Plantier‐Royon, Richard; Rémond, Caroline; Wegrowski, Yanusz
Abstract : Different mono‐xylosides and their corresponding xylobiosides obtained by a chemo‐enzymatic approach featuring various substituents attached to a triazole ring were probed as priming agents for glycosaminoglycan (GAG) biosynthesis in the xylosyltransferase‐deficient pgsA‐745 Chinese hamster ovary cell line. Xylosides containing a hydrophobic aglycone moiety were the most efficient priming agents. Mono‐xylosides induced higher GAG biosynthesis in comparison with their corresponding xylobiosides. The influence of the degree of polymerization of the carbohydrate part on the priming activity was investigated through different experiments. We demonstrated that in case of mono‐xylosides, the cellular uptake as well as the affinity and the catalytic efficiency of β‐1, 4‐galactosyltransferase 7 were higher than for xylobiosides. Altogether, these results indicate that hydrophobicity of the aglycone and degree of polymerization of glycone moiety were critical factors for an optimal priming activity for GAG biosynthesis. Abstract : 'Click'‐xylosides displayed a better activity as primers of GAG biosynthesis than the corresponding xylobiosides with a better cellular uptake and affinity of β4GalT7.